PERSEPSI WALI MURID PADA PELAKSANAAN BELAJAR DI RUMAH DALAM PERKEMBANGAN KOGNITIF ANAK DI MADRASAH IBTIDAIYAH - Mahmudah, Anis; I, Ichsan (Peneliti.net, 2023)
The problem that will be studied in this research is: What are the perceptions of parents during the study period at home in the development of children's cognitive aspects at MI Nurul Huda, Bengkulu City? The purpose of this study is to find out how parents perceive during the study period at home in the development of children's cognitive aspects at MI Nurul Huda, Bengkulu City. The research used is field research with a qualitative approach. Collecting data through observation, interviews and documentation. Based on the discussion, the results of the study can be concluded that most parents prefer that teaching and learning activities continue to be carried out at school, because there are several obstacles faced by students and parents during the learning period from home, namely, bad signal problems, not all parents can master the material provided by the teacher, to problems where students are more concerned with playing games when they are at home, whereas if studying at school students are more able to learn in a conducive, controlled and optimal way. So according to the perception of some parents, the learning process is more effective when it is done at school.